2019
DOI: 10.1111/jfbc.13056
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antithrombotic properties of Dendropanax morbifera Léveille (Araliaceae) and its ferments produced by fermentation processing

Abstract: The present study investigates and evaluates the antioxidant and antithrombotic effects of Dendropanax morbifera Léveille (Araliaceae) extracts (DME) and its ferment (FDME). Antioxidant activities were improved by FDME treatment, especially 66.74% of hydroxyl radical scavenging activity was observed at 100 μg of FDME treatment.In vitro antithrombotic activity was also improved by accelerated fibrinolysis and blood clot degradation as well as prolonged prothrombin time. Similar to those results, in vivo experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The increase in biological activity yielded by the fermentation of these LAB is affected by various factors. Some studies have suggested an increase in the content of phenolic compounds or the degradability of the food material used after fermentation as a major factor in raising the physiological activity of LAB (Choi & Kim, 2019; Eom et al., 2010; Hur et al., 2014; Lee et al., 2016; Mun et al., 2015). Other studies have reported that the unique bioconversion process of each strain of LAB can be a crucial factor that may change the constituents of food materials used for fermentation and their biological activities (Kerry et al., 2018; Quinto et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in biological activity yielded by the fermentation of these LAB is affected by various factors. Some studies have suggested an increase in the content of phenolic compounds or the degradability of the food material used after fermentation as a major factor in raising the physiological activity of LAB (Choi & Kim, 2019; Eom et al., 2010; Hur et al., 2014; Lee et al., 2016; Mun et al., 2015). Other studies have reported that the unique bioconversion process of each strain of LAB can be a crucial factor that may change the constituents of food materials used for fermentation and their biological activities (Kerry et al., 2018; Quinto et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Dendropanax morbiferus H.Lév. exerts various biological activities, including antifungal [34], antibacterial [34], cytotoxic [35,36], antidiabetic [37], antioxidant [38,39], anti-inflammatory [40,41], hepatoprotective [42], neuroprotective [43,44], and anticancer [45] activities. The bioactive compounds contained in Dendropanax morbiferus H.Lév.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12]. Furthermore, previous studies reported that D. morbifera exhibits antioxidant [13,14], anti-inflammatory [15,16], neuroprotective [6,17], osteosarcoma [18], antidiabetic [19,20], hepatoprotective [21,22], immunomodulatory [16,23], antibacterial and antifungal [24], antiplasmodial [25], cytotoxic [26], and larvicidal [27] functions. Recently, interest in D. morbifera as a functional material in cosmetics has increased thanks to its well-rounded health benefits for humans.…”
Section: Introductionmentioning
confidence: 97%